2015
DOI: 10.5146/tjpath.2015.01326
|View full text |Cite
|
Sign up to set email alerts
|

Ocular diseases among pathologists and pathologists' perceptions on ocular diseases: a survey study

Abstract: Objective: The impact of visual disorders and color vision deficiency on the occupational life has been previously investigated by several studies. In this study, we aimed to evaluate the prevalence of visual disorders among Turkish pathologists and their perceptions on visual disorders. Material and Method:A survey composed of 14 questions about ocular diseases and perceptions to these diseases has been introduced to the volunteering pathologists or pathology residents, participating in the 23rd Congress of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…This finding is supported – amusingly – by a recent paper demonstrating that pigeons ( Columba livia ) had a reduced accuracy for detecting breast cancer in using monochrome images compared to full colour . Furthermore, a survey of pathologists by Akman et al . reported that 61.3% of pathologists interviewed felt that colour‐blind pathologists should not perform pathology – thereby indicating that many pathologists feel that colour interpretation is important in the diagnostic process.…”
Section: Does Colour Matter In Pathology?mentioning
confidence: 84%
See 1 more Smart Citation
“…This finding is supported – amusingly – by a recent paper demonstrating that pigeons ( Columba livia ) had a reduced accuracy for detecting breast cancer in using monochrome images compared to full colour . Furthermore, a survey of pathologists by Akman et al . reported that 61.3% of pathologists interviewed felt that colour‐blind pathologists should not perform pathology – thereby indicating that many pathologists feel that colour interpretation is important in the diagnostic process.…”
Section: Does Colour Matter In Pathology?mentioning
confidence: 84%
“…Most commonly, blue colours appear more ‘washed out’ than others, resulting in the majority of colour defects in the elderly population being of blue–yellow type . While the effect of colour‐blindness among pathologists has been evaluated in a handful of studies, the effect of ageing on interpreting slides is unknown, and is likely to be more complex than simple physical visual changes.…”
Section: Colour and The Human Visual Systemmentioning
confidence: 99%
“…Eyeglasses were the most common form of correction (64.5% [60/93]); of those, 33.3% (31/93) reported using eyeglasses during microscopy. 5 The importance of visual ability in other highly visual specialties suggests that parallels can be drawn to similar practices in dermatology. Detection of cutaneous lesions might be affected by changes in vision, similar to detection of pulmonary lesions in radiology.…”
Section: Across Medical Disciplinesmentioning
confidence: 99%